A New Single 808 nm NIR Light-Induced Imaging-Guided Multifunctional Cancer Therapy Platform - He, Fei; Yang, Guixin; Yang, Piaoping; Yu, Yuxiu; Lv, Ruichan; Li, Chunxia; Dai, Yunlu; Gai, Shili; Lin, Jun (Advanced functional materials, 2015)
The NIR light‐induced imaging‐guided cancer therapy is a promising route in the targeting cancer therapy field. However, up to now, the existing single‐modality light‐induced imaging effects are not enough to meet the higher diagnosis requirement. Thus, the multifunctional cancer therapy platform with multimode light‐induced imaging effects is highly desirable. In this work, captopril stabilized‐Au nanoclusters Au25(Capt)18−(Au25) are assembled into the mesoporous silica shell coating outside of Nd3+‐sensitized upconversion nanoparticles (UCNPs) for the first time. The newly formed Au25 shell exhibits considerable photothermal effects, bringing about the photothermal imaging and photoacoustic imaging properties, which couple with the upconversion luminescence imaging. More importantly, the three light‐induced imaging effects can be simultaneously achieved by exciting with a single NIR light (808 nm), which is also the triggering factor for the photothermal and photodynamic cancer therapy. Besides, the nanoparticles can also present the magnetic resonance and computer tomography imaging effects due to the Gd3+ and Yb3+ ions in the UCNPs. Furthermore, due to the photodynamic and the photothermal effects, the nanoparticles possess efficient in vivo tumor growth inhibition under the single irradiation of 808 nm light. The multifunctional cancer therapy platform with multimode imaging effects realizes a true sense of light‐induced imaging‐guided cancer therapy. Au nanoclusters with photodynamic therapy and photothermal therapy effects are combined with upconversion nanoparticles for the first time to form a new multifunctional cancer therapy platform with multimode imaging and dual phototherapy function. The nanoparticles could be promising to achieve the light‐induced and imaging‐guided cancer therapy with low side effects.